Analisis Metode Cash On Delivery Aplikasi Shopee dalam Perspektif Ekonomi Syariah - aisyi, Chulwatul Aisyi; Ayu Kinanti, Risma; Hakam, Abdul; Valentine Mahardyta, Ajrina (IQTISADIE: Journal of Islamic Banking and Shariah Economy, 2024)
The most influential technological development in everyday life, especially among young people, is online shopping. This shopping model can be done anytime and anywhere as long as you are connected to the internet. With the rise of online shopping, various marketplaces have emerged. One of the e-commerce sites that is currently in great demand is the Shopee marketplace. Shopee has many payment systems on offer, including the Cash On Delivery (COD) payment system. This payment system is a system where goods are ordered first and then payment is made when the goods arrive at home. In the COD system in Shopee, several problems occur, including the incompatibility of the ordered goods with the goods sent by the seller. The aim of this research was to determine the implementation of online buying and selling transactions using the Cash On Delivery (COD) payment method in the Shopee application according to a Sharia Economic Perspective for employees of Hidayatul Ummah Gresik Vocational School. The author used several methods to collect data, including observation, interviews, and documentation. The results of this research are buying and selling through e-commerce Shopee in the sharia economy using Istishna'